INTEGRATED RESOURCE AND INFRASTRUCTURE MANAGEMENT IN THE TRANSFORMATION TO SMART CITIES - Chipriyanov, Mihail (E-Journal VFU, 2025)
The aim of this article is to explore the possibilities for the development of smart cities through the methods of synthesis, analysis, induction, and deduction. Based on these methods, key success factors are highlighted, such as the integration of intelligent technologies, optimization of transportation systems, and sustainable resource management. Special attention is given to the role of the public sector, which plays a key role in developing strategies and policies that promote innovation and collaboration between various stakeholders. These coordinated efforts are essential for achieving sustainable development in the context of smart cities.